Use of information and communication technologies in the process of spiritual and moral education at military schools - Lyudmila Ivanovna Redkina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article deals with the problem of information and communication technologies in the process of spiritual and moral education of servicemen use. For that purpose, the subject, objective, methodological basis and methods of research are indicated, topicality of the issue is proved and the analysis of the degree of the problem study in modern domestic and foreign science is carried out. On the basis of modern scientific research, the article outlines some tasks that information and communication technologies perform in the educational process of military men: the creation of a unified database of intangible heritage resources, the development of socially-personal and instrumental competence of servicemen, and the provision of mobile information to the military community and the society as a whole. The implementation of these tasks is complicated by the problem that is formulated in the article as information manipulation and misinformation in the information space. The following ways of the problem solution are offered: formation of critical thinking at students in military educational institutions; filling the educational electronic and technical environment with various forms of multimedia programs, interactive electronic educational resources and author materials that take into account the specifics of the military educational process and the age characteristics of students. The paper describes the reproductive and productive levels of using information tools in the educational process by the creators of interactive learning resources. The advantages of introducing information and communication technologies in the process of spiritual and moral education of servicemen are formulated as providing the opportunity for: creating new educational resources, methods and programs; successful adaptation of students in military educational institutions to social change and environment; acceleration of the process of cultural and personal knowledge and accumulated social experience transfer from the teacher to the learner and from generation to generation.